Lean Manufacturing as a Way of Employees’ Motivation in Energy Saving - Viktorovna Lenkova, Olga; Dmitrievich Kot, Anatolij; Gennadievna Yakunina, Olga; Semyonovich Yumsunov, Maxim (International Journal of Engineering and Technology, 2018)
The article indicates the importance of cost management in general, and energy consumption, in particular, at the enterprises of main oil transportation. For this purpose, it is necessary to search for losses in production processes and develop solutions for their elimination. The concept of "lean production", adapted to the industry features, is suggested as the main method of solving this problem. It outlines the importance of involving employees in the development of the strategy and motivation to search for losses and their elimination. In order to identify the awareness and motivation of employees for energy saving and rationalization, a questionnaire was developed. The results of the survey at one of the production departments of the oil transport enterprise are given. The work also presents a fragment of the Ishikawa diagram used to identify the reasons of the employees' insufficient interest in saving energy. The article covers the results of the study of the existing motivational policy of the organization and the research data of existing practices of constructing motivational systems in organizations in other spheres. Recommendations are given for adjusting the existing motivation system in the enterprise under study. An approximate plan for the implementation of the project proposals is suggested, and the directions for further research within the field are formulated.